PENGARUH MEDIA FLIPBOOK DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI INSUR INTRINSIK CERITA PENDEK SISWA KELAS III DI SDN 231 PALEMBANG - Ria Dwi Oktariani; Bayu iswana; Nurlela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is a planned activity in the learning support process that aims for students to develop their potential. In the learning process, one of the learning problems that students have is the low understanding of students in learning Indonesian on the intrinsic elements of short stories, because the learning carried out is not varied enough so that students tend to get bored and are not interested in learning. This study aims to determine whether there is an effect of flipbook media and improvements in Indonesian language learning outcomes on the intrinsic elements of short stories for grade III students at SDN 231 Palembang. This study is a type of quantitative research using the Quasy Experimental Design method. This study used two classes, namely class III C as an experimental class consisting of 26 students and class III B as a control class consisting of 26 students. The data collection technique used was the initial test before treatment (pretest) and after treatment (posttest) essay test containing 10 questions. This study obtained a significant t-test result of 0.000 <0.05, which means that H0 is rejected and Ha is accepted and obtained a Ngain test result with a score of 0.7591> 0.70, which means that there is a high increase. Based on the results of the study, the researcher concluded that learning using flipbook media has a significant effect and improves the learning outcomes of Indonesian language material on the intrinsic elements of short stories for grade III students at SD Negeri 231 Palembang. By using flipbook learning media, it can make it easier for students to understand the material and attract students' attention to learn more about the intrinsic elements of short stories